Pengembangan Buku Petunjuk Kinerja Siswa MA/ SMA Kelas XI Berbasis Phet Interactive Simulation Sebagai Sumber Belajar Mata Pelajaran Fisika Pada Materi Fluida Dinamis - Arbaul Fauziah; Hasna Husniah; Ahmad Fahrudin (LP4MK STKIP PGRI Lubuklinggau, 2021)
The aims of this research were to develop the student worksheet for class XI MA/ SMA based on PhET Interactive Simulation about dynamic fluid as a source of student learning and determine the validity level and student responses for it. The type of this research was Research and Development (R&D), consisted of four stages, they were preliminary study, product development, assessment and limited test of product, and evaluation of product. The research subjects consisted of three expert judgements (material expert, media expert, and learning partitioner) as well as 46 physic students at SMAN 1 Rejotangan. The results of preliminary study showed that more than 95% of respondents were unfamiliar with PhET application and agree with made of the student worksheet, so the student worksheet based on PhET Interactive Simulation about dynamic fluid was developed. The results of material expert, media expert, and learning partitioner validation recpectively were 79.58% (valid), 82% (extremely valid), and 85.83% (extremely valid) and appropriate for used. The results of product evaluation by 46 respondents showed positive responses, namely 75% respondents stated that the work steps of the student worksheet based on PhET Interactive Simulation about dynamic fluid were clear and attractive, so it could be used easily.